Conduction system pacing for cardiac resynchronization therapy: State of the art, current controversies, and future perspectives - Bressi, Edoardo; Grieco, Domenico; Luermans, Justin; Burri, Haran; Vernooy, Kevin (Frontiers in Physiology, 2023)
Biventricular pacing (BVP) is the established treatment to perform cardiac resynchronization therapy (CRT) in patients with heart failure (HF) and left bundle branch block (LBBB). However, BVP is an unnatural pacing modality still conditioned by the high percentage of non-responders and coronary sinus anatomy. Conduction system pacing (CSP) – His bundle pacing (HBP) and Left bundle branch area pacing (LBBAP)- upcomes as the physiological alternative to BVP in the quest for the optimal CRT. CSP showed promising results in terms of better electro-mechanical ventricular synchronization compared to BVP. However, only a few randomized control trials are currently available, and technical challenges, along with the lack of information on long-term clinical outcomes, limit the establishment of a primary role for CSP over conventional BVP in CRT candidates. This review provides a comprehensive literature revision of potential applications of CSP for CRT in diverse clinical scenarios, underlining the current controversies and prospects of this technique.